Making a Pentecostal Man: Machismo and the Moral Discourse of Prosperity Gospel in Honduras - Son, Seung Jin (PentecoStudies, 2016)
Since 2009, the murder rate of Honduras has been the highest in the world, according to the United Nations Office on Drugs and Crime. Numerous scholars have pointed out that machismo, the hyper-masculinity of Latin America, has been one of the main causes of the cruel narco (drug gang) activities. Simultaneously, Pentecostal churches in Honduras have achieved rapid growth throughout the region, and Iglesia Puerta del Cielo, Familia de Amor y Poder (PDC) is the biggest independent Pentecostal congregation in La Ceiba, Honduras. Despite the noticeable theological influence from North America, the people of PDC have developed their own theological concept of prosperity to respond to their context of insecurity. Ironically, to respond to their existential crisis, PDC suggests a new masculinity, which is still reflecting the image of ideal macho who is a well-disciplined man and the providing father of the family. This article will explore the meaning of machismo, and examine how PDC has disciplined and gendered a male body into the theological and moral discourse of Prosperity Gospel.